Phenomenological Psychopathology (Interview with Prof. Dr. Guilherme Messas) - Puchivailo, Mariana Cardoso (Revista PsicoFAE: Pluralidades em Saúde Mental, 2019)
The current interview has occurred in november between the interviewers Victor Portugal and Andre Fukuda with Prof. Dr. Guilherme Messas. The dialogue tried to explore coming from basic questions concerning phenomenological psychopathology to contemporary debates and opinions present in the literature. In general, Prof. Messas sought throughout the interview to define and defend phenomenological psychopathology not as the only hegemonic option in the field, but as an interesting path which maintains itself close to human experience, which analyzes the structures of subjectivity and carries a high clinical value. Prof. Messas has in various moments highlighted that phenomenological psychopathology is not contrary to the studies in biology or pharmacology, an erroneous opposition which is frequently lifted in theoretical and practical contexts, but that it is actually possible to have a mutually beneficial relationship. What does phenomenological psychopathology is in fact opposed is to what the Professor called ‘philosophical operationalism’ and ‘cerebrocentrism’, fundamental pillars for the DSM’s current psychopathology. Besides, Prof. Messas highlight his position regarding the relationship between phenomenological philosophy and psychopathology. According to him, as a historical result of the application of phenomenology to psychopathology, phenomenological psychopathology became independent, i.e. it has a life of its own regarding that fundament who originated it in the first place. It would not be the case, then, that it should always be necessary to return to classical authors of phenomenological philosophy in order to validate what phenomenological psychopathology performs. Lastly, the interviewed affirmed that he believes in the existence of a very bright future for phenomenology in psychopathology, specially for the brazilian one. This future demands in one hand reading the classics, but on the other hand it also demands audacity to be thrown in contemporary debates which occur worldwide, enabling that the brazilian contributions to the field, which is of excellent quality, develop itself even more. This interview represents an attempt to introduce but also to clarify and structure the subject of phenomenological psychopathology in Brazil with one of its leading authors.